Shield Calculation Design for gamma-ray sterilzer plant (Baghdad Science Journal, 2005)
The present calculation covers the building shield during irradiation process and under water storage of three milion curries Cobalt-60 radiation source the calculation results in design requirement of 8m depth of water in the source stoeage pool